Monitoring Tissue Perfusion in Shock From Physiology to the Bedside (Springer International Publishing, 2018)
This book describes various aspects of the basic physiological processes critical to tissue perfusion and cellular oxygenation, including the roles of the circulatory system, respiratory system, blood flow distribution and microcirculation. In the context of monitoring critically ill patients in the early hours of circulatory shock, it is essential to recognize changes in traditional parameters such as mean arterial pressure and cardiac output, and to assess the need for active intervention. However, even if global macrocirculatory variables are restored, abnormalities in tissue oxygenation may persist. Tissue hypoperfusion is connected to the development of organ failure and, if it goes unrecognized, may worsen the prognosis. As a result, there is a growing interest in methods for monitoring regional perfusion in peripheral tissues to predict or diagnose ongoing hypoperfusion. In this work, eminent experts from a range of disciplines convey a working knowledge of how regional monitoring in shock can complement the conventional global parameters of oxygen transport, and demonstrate that real-time bedside assessment of tissue oxygenation is readily achievable using noninvasive monitoring techniques. Accordingly, the book offers a valuable, easy-to-use guide for the entire ICU team and other clinicians.